Randomized Double-Blind Placebo-Controlled Trial of Desmopressin for Post–Kidney Biopsy Bleeding - Narayan Prasad; Jeyakumar Meyyappan; Deependra Kumar Yadav; Brijesh Yadav; Ravi Kushwaha; Manas Patel; Vamsidhar Veeranki; Dharmendra Bhadauria; Manas Behera; Monika Yachha; Anupama Kaul; Jai Kishun; et al. (Kidney International Reports, 2025)
Introduction: This study evaluated the efficacy and safety of desmopressin in reducing postbiopsy bleeding in patients undergoing kidney biopsy, a common complication requiring effective prevention strategies. Methods: In this double-blind, randomized, placebo-controlled trial conducted from February 2019 to January 2023 at a teaching institute in Lucknow, India, 203 patients aged 18 to 65 years undergoing indication kidney biopsy were randomized to receive desmopressin (300 μg) or placebo intranasally an hour before the procedure. Outcomes included postbiopsy bleeding (primary) and hemoglobin drop, hypotension, hematuria, hematoma, transfusion need, and radiological or surgical interventions (secondary). Results: Bleeding incidence was significantly lower in the desmopressin group (11.9%) compared with placebo (33.3%, P = 0.0003). Hematoma formation was reduced (11.9% vs. 30.4%, P = 0.001), with a relative risk (RR) of bleeding of 0.356 (95% confidence interval [CI]: 0.196–0.648, P = 0.0007). Stratified analysis showed reduced bleeding across estimated glomerular filtration rate (eGFR) categories (> 30 and < 30 ml/min per 1.73 m2), with numbers needed-to-treat of 5.667 and 3.978, respectively. Hyponatremia and headaches were more frequent in the desmopressin group. Factor VIII and von Willebrand factor (vWF) levels were significantly elevated 2 and 4 hours after administration. No serious adverse events occurred. Conclusion: Desmopressin effectively reduces postbiopsy bleeding and hematoma formation with manageable side effects, supporting its role as a prophylactic option in kidney biopsies. Further studies are needed to confirm its broader clinical applications.